EFEKTIVITAS PERAN PANGLIMA LAOT DALAM MITIGASI KERUSAKAN KAWASAN PESISIR DAN LAUT DI KOTA SABANG - Liztiawati .; Agussabti .; Safrida . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The Panglima Laot Institute is one of the customary institutions responsible for the management of coastal and marine resources. This institution has a very important role in the mitigation of coastal and marine degradation. To carry out their duties The Institute can not do it on its own but requires community participation. The objectives of this research are: (1) To know the effectiveness of the role of Panglima Laot Institution in developing community participation toward the mitigation of coastal and marine area destruction in Sabang City, (2) to know the factors influencing the effectiveness of Panglima Laot's role in growth of community participation on coastal area damage mitigation and sea in Sabang City, (3) Recommend Strategy for strengthening Panglima Laot in the implementation of its role to mitigate coastal and marine area damage in Sabang City. This research uses quantitative and qualitative approach. Respondents in this study are the Chief Commander of Laot Kota Sabang, fishermen community, and related agencies. Data analysis using the average formula categorized using Likert scale and Linear Regression Analysis to determine the factors that influence. The results of this research are (1) Panglima Laot institution has performed its role quite effectively to cultivate community participation in the mitigation of coastal and marine area damage; (2) a significant factor influencing the participation of the community is 37.3%.